2008
DOI: 10.3346/jkms.2008.23.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vascular Endothelial Growth Factor Gene Polymorphisms with Susceptibility and Clinicopathologic Characteristics of Colorectal Cancer

Abstract: Since vascular endothelial growth factor (VEGF) is known to be a potent pro-angiogenic factor, we evaluated the potential association of two VEGF gene polymorphisms (-634G>C and 936C>T) with the susceptibility and the clinicopathologic characteristics of colorectal cancer (CRC). The VEGF genotypes were determined using fresh colorectal tissue from 465 patients who had undergone a surgical resection and peripheral blood lymphocytes from 413 healthy controls by PCR/DHPLC assay. For the -634G>C polymorphism, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 23 publications
6
36
2
Order By: Relevance
“…Other studies, mostly involving a relatively small population sample, found different associations between the investigated SNPs and tumor development. Chae et al (29) found that the -634 G/ +936 T combination was associated with a decreased susceptibility to CRC in a Korean population, which in part contradicts our findings. We chose to combine +936 C/T with -2578 C/A rather than -634 G/C.…”
Section: Discussioncontrasting
confidence: 57%
“…Other studies, mostly involving a relatively small population sample, found different associations between the investigated SNPs and tumor development. Chae et al (29) found that the -634 G/ +936 T combination was associated with a decreased susceptibility to CRC in a Korean population, which in part contradicts our findings. We chose to combine +936 C/T with -2578 C/A rather than -634 G/C.…”
Section: Discussioncontrasting
confidence: 57%
“…Our findings were similar to those of previous studies conducted in other populations in which no correlation between the VEGF +936 C>T variant and CRC susceptibility was observed (Hofmann et al, 2008;Dassoulas et al, 2009;Wu et al, 2009). Nonetheless, the TT genotype was shown to correlate with the advanced stage of CRC, a higher serum level of CA19-9, a higher histological grade of CRC tumors, and poorer patient prognosis (Chae et al, 2008). Furthermore, Nakasaki et al, (2002) demonstrated that the expression of VEGF varied significantly across different stages of CRC progression, and was correlated with the metastasis and tumor vascularity of CRC neoplasms.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, increasing number of studies have highlighted the association between the VEGF -634 G/C polymorphism and various cancers including lung, gastric, colorectal, and cervical cancer (Jin et al, 2005;Lee et al, 2005;Jacobs et al, 2006;Kataoka et al, 2006;Sfar et al, 2006;Tzanakis et al, 2006;Balasubramanian et al, 2007;Garcia-Closas et al, 2007;Hsiao et al, 2007;Amano et al, 2008;Chae et al, 2006Chae et al, , 2008Hofmann et al, 2008;Ke et al, 2008;Zhai et al, 2008a,b;Al-Moundhri et al, 2009;Dassoulas et al, 2009;Guan et al, 2009;Maltese et al, 2009;Ungerbäck et al, 2009;Bruyère et al, 2010;Kim et al, 2010;Zhou et al, 2011;Supic et al, 2012;Deng et al, 2013;Luo et al, 2013;Wang et al, 2014). Due to the substantial differences in sample size, these studies failed to accurately define the genetic susceptibility of the VEGF -634 G/C polymorphism in development of cancer.…”
Section: Introductionmentioning
confidence: 99%